PEMBELAJARAN BAHASA ARAB MENGGUNAKAN METODE MENYANYI UNTUK ANAK DI TPQ AL FATH SURABAYA - Rifqi Riza Furqon; Najih Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the implementation of the singing method in Arabiclanguage instruction at TPQ Al Fath Surabaya and to examine students’ responsestoward its application. Employing a descriptive qualitative approach, data werecollected through observation, interviews, and documentation. The findings revealthat the integration of singing with thematic dialogues significantly enhancesstudents’ learning motivation, active participation, and vocabulary acquisition.Positive responses from students, teachers, and parents indicate that this method isnot only effective in improving Arabic language skills among young learners but alsocreates an engaging and contextual learning environment.